A Contribution to the Study of Production Diversification in the Context of Developing Economies: Analyzing Factors Associated with Product Relatedness (Desarrollo Económico. Revista de Ciencias Sociales, 2021)
Countries grow by expanding the products they produce and export, at least in the early stages of development. Such diversification tends to occur in new products related to the existing ones, both at the aggregate and at firm level. However, for developing economies, “long jumps” between less related activities to unrelated activities are important, allowing them to change more radically their productive structure and develop. In this paper, we contribute to the study of diversification in developing countries, analyzing factors associated with relatedness. We distinguish between productive and non-productive factors. We use a unique and novel database about diversification at firm level surveyed at General Pueyrredón Party in 2013/14. Our results indicate that diversification in distant products is mostly associated with non-productive factors, while diversification in closed products is associated with productive characteristics of goods. In all cases, brand recognition and skills to operate in the institutional environment are also relevant for diversification.
Keywords: Relatedness, Productive Diversification, Unrelated Products, Unrelated Diversification, Co-ocurrence, Quantile Regression